Effect of In-cylinder Flow Structures on Late Cycle Soot Oxidation in a Quiescent Heavy-duty Diesel Engine. Issue 2 (25th January 2022) - Fatehi, Hesameddin; Lucchini, Tommaso; D'Errico, Gianluca; Karlsson, Anders; Bai, Xue-Song; Andersson, Öivind
ABSTRACT: This paper reports on CFD simulations of in-cylinder flow and combustion in an open-bowl heavy duty diesel engine at high load. The focus of the study is to unravel the effect of swirl motion on the soot formation and on the late cycle soot oxidation. To incorporate detailed kinetic mechanism while maintaining a manageable computational time, Representative Interactive Flamelets (RIF) method is employed to describe the chemical reactions, ignition, flame propagation, and emissions in the engine. In modeling the soot, a phenomenological model is employed where soot formation, nucleation, coagulation, and oxidation with O2 and OH are considered. Four values for swirl numbers, SN = 0, 0.5, 1.7, and 3.4, at three injection pressures and three injection timings are considered. It is shown that increasing the swirl number leads to an increase in both the amount of soot in the exhaust gas and the peak value of soot in the engine cylinder. The mechanisms of soot formation and oxidation and swirl/in-cylinder flow interaction in the given engine configuration are investigated based on the numerical results. It is shown that in-cylinder turbulence is the key parameter affecting the formation and oxidation of soot. Despite the higher mean flow kinetic energy in the high swirl cases than in the no-swirl case, the no-swirl case has a higher turbulent kinetic energy at late cycle. This is due to the presence of coherent structures created from the spray-wall interaction, which can survive longer time after the end of injection (EOI).